PENGARUH ENDORSER TENAGA AHLI TERHADAP MINAT PEMBELIAN SENSODYNE - Auliasari, Fitri; Firmansyah, Fani (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
One of the realities in the business world is the increasingly sharp competition. One of the causes of the increasingly sharp competition is the more companies that produce and market similar or similar products or the number of companies that are able to offer products to consumers with relatively similar be h nefits Sensodyne seeks to create its own market share in Indonesia, by educating the market related awareness taking care of sensitive teeth. This study aims to identify the influence of endorser experts on purchasing interest in Sensodyne toothpaste. This research uses quantitative research type with descriptive analysis method and linear regression analysis. The population in this study are the customers of Hypermart Malang Town Square. The sampling technique is purposive sampling with the number of samples of 100 respondents. The result of research indicate that there is influence of attraction to consumer interest of Sensodyne to consumer in Hypermart Malang Town Square. While the credibility variable has no effect on the purchase interest of Sensodyne to the consumer in Hypermart Malang Town Square.